The Differences Hematocrit and Platelet Levels of Biology Students and Sports Students Universitas Negeri Padang - Anika Fadila Sari; Elsa Yuniarti (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Blood is 90% of the fluids that make up the human body. Blood cells are divided into erythrocytes, leukocytes, and platelets. To determine blood levels in a person's body can be done by measuring the hematocrit level. The hematocrit value in the body can be influenced by external factors such as routine physical exercise while internal factors such as fulfilling a balanced nutritional intake. This study aims to determine differences in hematocrit and platelet levels of biology students and sports students. This research is a quantitative descriptive. Subjects in this study were individuals who met the inclusion and exclusion criteria. The samples used were 15 biology students and 15 sports students. Analysis of the data obtained from the hematology analyzer examination was then carried out using the RStudio program for further statistical tests, namely the t-test with α = 0.05 with a 95% confidence interval. Based on the results of data analysis on hematocrit levels of biology and sports students, it was found that p<0.0002. While the platelet levels of biology students with sports students obtained p<0.0097. So it can be concluded that there are significant differences in the hematocrit and platelet levels of biology students and sports students. Keywords: Blood, Hematocrit, Hematology, Platelets, t-test